2016
DOI: 10.1038/srep23433
|View full text |Cite
|
Sign up to set email alerts
|

ATX-LPA1 axis contributes to proliferation of chondrocytes by regulating fibronectin assembly leading to proper cartilage formation

Abstract: The lipid mediator lysophosphatidic acid (LPA) signals via six distinct G protein-coupled receptors to mediate both unique and overlapping biological effects, including cell migration, proliferation and survival. LPA is produced extracellularly by autotaxin (ATX), a secreted lysophospholipase D, from lysophosphatidylcholine. ATX-LPA receptor signaling is essential for normal development and implicated in various (patho)physiological processes, but underlying mechanisms remain incompletely understood. Through g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 62 publications
(72 reference statements)
2
26
0
Order By: Relevance
“…Mechanistically, LPA 1 signaling acts by promoting S‐phase entry and cell proliferation of chondrocytes by regulating fibronectin assembly. Loss of LPA 1 signaling in LPA 1 −/− mice leads to disorganization of chondrocytes similarly to what is observed in OPS (Nishioka et al., ). It is known that focal adhesion assembly involves the activation of β1‐integrin downstream of LPA 1 signaling; this is also decreased in LPA 1 −/− chondrocytes as compared to normal cells.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Mechanistically, LPA 1 signaling acts by promoting S‐phase entry and cell proliferation of chondrocytes by regulating fibronectin assembly. Loss of LPA 1 signaling in LPA 1 −/− mice leads to disorganization of chondrocytes similarly to what is observed in OPS (Nishioka et al., ). It is known that focal adhesion assembly involves the activation of β1‐integrin downstream of LPA 1 signaling; this is also decreased in LPA 1 −/− chondrocytes as compared to normal cells.…”
Section: Discussionsupporting
confidence: 68%
“…For column‐forming, chondrocytes require cell–cell adhesion mechanisms that influence cell spreading and rearrangement (Romereim et al., ). Cell adhesion also affects the proliferation and survival of chondrocytes (Nishioka et al., ). Our data suggest that the appropriate control of cell adhesion in normal chondrocytes, which have SHIP2, would not be present in OPS cells and this would disorganize dividing cells at the growth plate.…”
Section: Discussionmentioning
confidence: 99%
“…As an EMT marker, fibronectin is involved in cell adhesion and migration, including embryogenesis,17 wound healing,18 blood coagulation,19 osteogenesis,20 and metastasis 21,22. EMT is a process involved in embryonic development, during which cells lose their epithelial features and adopt characteristics of mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…LPA is mainly synthesized from lysophospholipids such as lysophosphatidylcholine (LPC) by a secretory enzyme autotaxin (ATX; Umezu‐Goto et al , 2002). Studies of knock‐out (KO) mice and human genetic diseases of these LPA‐related genes have shown that LPA has various pathophysiological roles including angiogenesis (Yukiura et al , 2011), hair follicle formation (Inoue et al , 2011; Hayashi et al , 2015), bone development (Nishioka et al , 2016), and neural development (Yung et al , 2015). We previously showed that LPA 3 , which is highly expressed in the uterine epithelium during the peri‐implantation period (Ye et al , 2005), has a critical role in the early pregnancy.…”
Section: Introductionmentioning
confidence: 99%